2001
DOI: 10.1053/jhep.2001.28199
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal papillary neoplasia of the liver associated with hepatolithiasis

Abstract: Intrahepatic cholangiocarcinoma (ICC) is a primary malignancy of the liver second in prevalence only to hepatocellular carcinoma. 1 In East-Asian countries where hepatolithiasis is not uncommon, ICC is known to develop in patients with hepatolithiasis: the incidence of ICC in hepatolithiasis in Taiwan and Japan is approximately 5%. [2][3][4] ICCs, at least those arising in hepatolithiasis, are known to show multistep progression, undergoing a biliary dysplasia-carcinoma sequence. 1 With recent advances in imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
262
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(270 citation statements)
references
References 27 publications
(47 reference statements)
5
262
2
1
Order By: Relevance
“…A previous history of biliary disease and chronic hepatitis C was noted in seven patients. Chronic inflammation of the biliary epithelium has been reported to be a risk factor for IPNB22, 23, 25, 26 and conventional cholangiocarcinoma,27 and this finding might thus also be applicable to mucinous cholangiocarcinoma. Chou and Chan28 reported that all three cases of mucinous cholangiocarcinomas in their study were heavily infested with Clonorchis sinensis .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A previous history of biliary disease and chronic hepatitis C was noted in seven patients. Chronic inflammation of the biliary epithelium has been reported to be a risk factor for IPNB22, 23, 25, 26 and conventional cholangiocarcinoma,27 and this finding might thus also be applicable to mucinous cholangiocarcinoma. Chou and Chan28 reported that all three cases of mucinous cholangiocarcinomas in their study were heavily infested with Clonorchis sinensis .…”
Section: Discussionmentioning
confidence: 74%
“…IPNB is pathologically characterized by prominent intraductal papillary proliferation with delicate fibrovascular cores and frequent mucin hypersecretion,15, 16, 21 and it is regarded as the biliary counterpart of intraductal papillary mucinous neoplasm of the pancreas. When accompanied by invasive lesions, IPNB is known to be associated with conventional tubular adenocarcinoma or mucinous cholangiocarcinoma 22, 23, 24. IPNB is characterized by the intestinal phenotype (mucin2 [MUC2]+/cytokeratin20+), with the carcinogeneses leading to tubular adenocarcinoma and mucinous cholangiocarcinoma associated with increasing MUC1 expression and MUC1‐negativity, respectively 21…”
Section: Discussionmentioning
confidence: 99%
“…Biliary intraductal papillary neoplasm is considered as a biliary counterpart of intraductal papillary mucinous neoplasms of the pancreas based on a predominant intraductal growth, ductal dilatation, and occasional overproduction of mucin. 4 A previous study revealed that cystic liver tumours with bile duct communication share characteristics with intraductal papillary neoplasms, but not mucinous cystic neoplasms. 5 There had been controversy regarding the distinction between mucinous cystic neoplasms and intraductal papillary neoplasms until the presence of an ovarian-like stroma was accepted as a prerequisite for the diagnosis of mucinous cystic neoplasms and the distinct entity of biliary intraductal papillary neoplasms was proposed.…”
mentioning
confidence: 98%
“…3 Recently, a unique biliary tumour named intraductal papillary neoplasm of the bile duct has been included among biliary cystic tumours. 4 Biliary papillomas, biliary papillomatosis, and some of papillary cholangiocarcinomas are included in this category. Biliary intraductal papillary neoplasm is considered as a biliary counterpart of intraductal papillary mucinous neoplasms of the pancreas based on a predominant intraductal growth, ductal dilatation, and occasional overproduction of mucin.…”
mentioning
confidence: 99%
“…Recent studies have shed new light on cholangiocarcinomas with intraductal proliferative elements, including intraductal papillary neoplasm of the bile duct, [1][2][3][4][5][6] which was first documented by Nakanuma et al 7 and listed in the 2010 World Health Organization classification. 1 These tumors are mainly subdivided into two groups, with the intraductal growth type accounting for 6-14% of intrahepatic cholangiocarcinomas [8][9][10][11][12] and the macroscopic papillary growth type accounting for 8-20% of extrahepatic cholangiocarcinomas.…”
mentioning
confidence: 99%